Ranking mAb-excipient interactions in biologics formulations by NMR spectroscopy and computational approaches - Chunting Zhang; Steven T. Gossert; Jonathan Williams; Michael Little; Marilia Barros; Barton Dear; Bradley Falk; Ankit D. Kanthe; Robert Garmise; Luciano Mueller; Andrew Ilott; Anuji Abraham (Taylor & Francis Group, 2023)
ABSTRACTExcipients are added to biopharmaceutical formulations to enhance protein stability and enable the development of robust formulations with acceptable physicochemical properties, but the mechanism by which they confer stability is not fully understood. Here, we aimed to elucidate the mechanism through direct experimental evidence of the binding affinity of an excipient to a monoclonal antibody (mAb), using saturation transfer difference (STD) nuclear magnetic resonance (NMR) spectroscopic method. We ranked a series of excipients with respect to their dissociation constant (KD) and nonspecific binding constants (Ns). In parallel, molecular dynamic and site identification by ligand competitive saturation (SILCS)-Monte Carlo simulations were done to rank the excipient proximity to the proteins, thereby corroborating the ranking by STD NMR. Finally, the excipient ranking by NMR was correlated with mAb conformational and colloidal stability. Our approach can aid excipient selection in biologic formulations by providing insights into mAb-excipient affinities before conventional and time-consuming excipient screening studies are conducted.